2021
DOI: 10.1038/s41467-021-24565-z
|View full text |Cite
|
Sign up to set email alerts
|

Parallel processing of working memory and temporal information by distinct types of cortical projection neurons

Abstract: It is unclear how different types of cortical projection neurons work together to support diverse cortical functions. We examined the discharge characteristics and inactivation effects of intratelencephalic (IT) and pyramidal tract (PT) neurons—two major types of cortical excitatory neurons that project to cortical and subcortical structures, respectively—in the deep layer of the medial prefrontal cortex in mice performing a delayed response task. We found stronger target-dependent firing of IT than PT neurons… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 71 publications
2
6
0
Order By: Relevance
“…It seems that IT neurons are strongly engaged in preparatory stages of various tasks as they are more active in sensory regions during sensory sampling phases ( Musall et al, 2021 ; Mohan et al, 2022 ). This trend is consistent in other areas such as mPFC where they retain goal specific responses prior to action initiation ( Bae et al, 2021 ) and preparatory movement activities in motor structures ( Currie et al, 2021 ; Heindorf and Keller, 2022 ). Inhibiting the IT neurons during sampling periods only weakly affects the behavioral outcome, suggesting a minor role in regulating behavioral output.…”
Section: Behaviorsupporting
confidence: 83%
See 1 more Smart Citation
“…It seems that IT neurons are strongly engaged in preparatory stages of various tasks as they are more active in sensory regions during sensory sampling phases ( Musall et al, 2021 ; Mohan et al, 2022 ). This trend is consistent in other areas such as mPFC where they retain goal specific responses prior to action initiation ( Bae et al, 2021 ) and preparatory movement activities in motor structures ( Currie et al, 2021 ; Heindorf and Keller, 2022 ). Inhibiting the IT neurons during sampling periods only weakly affects the behavioral outcome, suggesting a minor role in regulating behavioral output.…”
Section: Behaviorsupporting
confidence: 83%
“…In recent years, there has been a surge of evidence of the distinct functional roles of IT and ET neurons in cognitive behavior ( Li et al, 2015 ; Takahashi et al, 2020 ; Bae et al, 2021 ; Currie et al, 2021 ; Musall et al, 2021 ; Heindorf and Keller, 2022 ; Mohan et al, 2022 ; Park et al, 2022 ). With recent development of combining whole-brain imaging with newly developed mouse lines, it is now possible to record brain-wide activity of IT neurons (including both L5 and L2/3 IT neurons) and L5 ET neurons.…”
Section: Behaviormentioning
confidence: 99%
“…In this study, we found that the frontal lobe regions (including the ORBmid.L, ORBinf.R, and MFG.L) in MCI reverters showed increased ALFF and fALFF, while the cerebellum_9_R showed decreased ALFF and fALFF. The frontal lobe is thought to be involved in many high-level cognitive functions ( Bae et al, 2021 ; Wang Y. et al, 2021 ). Increased frontal cortex connectivity is considered to be associated with increased cognitive control, higher IQ, and higher cognitive performance in young individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a reduced and increased, respectively, significance of these regions in the whole-brain. ITG.L and SFGmed.L regions are involved in memory tasks ( Sidhu et al, 2013 ; Bae et al, 2021 ), and the cerebellum, INS.L, and INS.R are more related to motor and attentional processes ( Wagner and Luo, 2020 ; Song et al, 2021 ). Previous studies have suggested that patients with AD may use other neurological resources to compensate for the loss of cognitive function in the early stages of the disease ( Grady et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since at least 10 sniffing trials were required for each group, neurons with less than 10 sniffing trials for any of left and right sidedness or social and object targets were removed from analysis. We have modified an open source code ( Bae et al, 2021 ), which uses MATLAB ‘fitcsvm’ function for SVM decoding.…”
Section: Methodsmentioning
confidence: 99%